2019
DOI: 10.1021/acs.iecr.9b01898
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Copper-Based Catalyst Deactivation during CO2 Reduction to Methanol

Abstract: Despite the fact that the methanol synthesis process includes industrially some of the most important catalytic chemical reactions, it is still not clear how different gaseous species impact catalyst component structure. With the goal to reduce CO2 emissions through hydrogenation to CH3OH, a higher H2O formation rate than in the production from compressed CO-rich feed should also be considered. It is known that steam accelerates the sintering of metals, several oxide compounds, and their interfaces. To determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 39 publications
2
87
0
Order By: Relevance
“…Quantification phase analysis was conducted with the value K method, following the Chinese oil and gas industry standard SY/T 5163-2018 [38][39][40], in which the relative deviation of test results is less than 10%, when mineral content is more than 40%. When the mineral standard and corundum are formulated into a two-phase mixture in a ratio of 1:1 by mass, the reference strength of the mineral i can be calculated as Equation (1). Therefore, the percentage of the mineral i can be described by Equation (2).…”
Section: Sample Collection Preparation and Analytical Equipmentmentioning
confidence: 99%
“…Quantification phase analysis was conducted with the value K method, following the Chinese oil and gas industry standard SY/T 5163-2018 [38][39][40], in which the relative deviation of test results is less than 10%, when mineral content is more than 40%. When the mineral standard and corundum are formulated into a two-phase mixture in a ratio of 1:1 by mass, the reference strength of the mineral i can be calculated as Equation (1). Therefore, the percentage of the mineral i can be described by Equation (2).…”
Section: Sample Collection Preparation and Analytical Equipmentmentioning
confidence: 99%
“…The later pathway, which is slow and approaches the steady-state, is caused by the surface coverage of some reaction products and intermediates, especially water, and carbonated species (Roberts et al, 1993). It was found that the cause of catalyst deactivation was sintering of both Al 2 O 3 and Cu with water due to the decreasing Al 2 O 3 surface, and Cu particle size with increasing content of H 2 O (Prasňikar et al, 2019).…”
Section: Deactivation Of Methanol Synthesis Catalystsmentioning
confidence: 99%
“…The Cu particle growth was fitted to a coalescence model for sintering (Figure 8B), which confirms coalescence as the operating mechanism. The increased particle migration is due to weak contact between the metal and support or increased surface diffusion of catalytic material (Prasňikar et al, 2019). The structures of ZnO and Al 2 O 3 species and metallic Cu can be stabilized to improve the catalyst lifetime, which can be accomplished by forming stable Cu interface with support material, and by stabilizing the dynamic nature of ZnO under working conditions using hydrophobic or hydrothermally stable materials.…”
Section: Deactivation Of Methanol Synthesis Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 The formation of a large amount of water byproduct during CO 2 hydrogenation in comparison to synthesis gas hydrogenation poses another challenge to catalyst stability, as water can accelerate the deactivation of Cu/ZnO/Al 2 O 3 catalysts. 9 12 …”
Section: Introductionmentioning
confidence: 99%